Microbiological assessment of fish kinilaw from tanguigue (Scomberomorus commerson) - Cruz , Aida Rizza Zaragoza (Iloilo Sotech, 2003)
Local vinegar from tuba and commercial (Del Monte Red Cane) vinegar were used separately in preparing fish kinilaw.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fish kinilaw; Tanguigue; Scomberomorus commerson